Kerala Gujarat Models: A Comparative Study With Respect To Socio-Economic Environment - Muhammed Salim. A.P (Imperial Journal of Interdisciplinary Research (IJIR), 2016)
Kerala-Gujarat Models of development were lauded and animadverted on accomplishments and impairments in varying sectors. This study exhumes the distinction of Gujarat Model in economic sectors shown by high per capita income, better and constant share of agriculture and industry, and giant and diversified energy sector. Kerala’s peerless and enviable outcomes in health and education have really made the Kerala Model distinguished all over the world. While Gujarat Model is weak on education-health standards even though improving, Kerala Model made the globally comparable outcomes in it at the backing of poor economic standards. At that, Kerala which is blessed with top standard social indicators trails by high crime rate against women and children and suicide rate. Biggest paradox in these models of development is highest unemployment rate in Kerala with lowest poverty ratio and lowest unemployment rate in Gujarat with higher poverty ratio. Even though these two transverse models lead or trail in transverse indicators of development, lead the national average mostly.